UPAYA INDONESIA MEMPERTAHANKAN PROGRAM GENERALIZED SYSTEM of PREFERENCE (GSP) AMERIKA SERIKAT - Armazumi, Fadly; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
In 2018, the United States of America (USA) announced that it would review of Indonesia's eligibility to receive the United States Generalized System of Preference (GSP) facility. The review was taken since the United States considered that Indonesia implemented various trade and investment barriers having negative impacts on USA trade due to the policy of import regulations for horticultural products and the imposition of the National Payment Gateway (NPG). Hence, this research studies Indonesia’s efforts to ensure and to maintain Indonesia's eligibility as a recipient country by meeting the provisions of the USA under GSP program. This research uses the Liberalism Perspective and the Nation-State level of analysis. The used theory is International Trade Theory wtih the concept of National Interest. Moreover, this research uses qualitative research with data collection technique is literature reseach taken from goevernment official websites, news websites, journals or other research report and books. This research concludes that the efforts made by the Indonesian government are initiated by approaching the USA government, eliminating trade barriers to restricting imports of horticultural products and enforcing national payment gateways and ensuring the protection of Intellectual Property Rights (IPR). These steps were used as a negotiating force as well as ensuring Indonesia accepting GSP facilities. Keywords: United States of America, GSP, Indonesia, NPG, IPR